Detection of Sn(II) ions via quenching of the fluorescence of carbon nanodots - Mohd Yazid, Siti Nur Akmar; Suk , Fun Chin; Suh, Cem Pang; Sing, Muk Ng (Springer-Verlag Wien, 2012)
Abstract We report that fluorescent carbon nanodots (Cdots) can act as an optical probe for quantifying Sn(II) ions in aqueous solution. C-dots are synthesized by carbonization and surface oxidation of preformed sago starch nanoparticles. Their fluorescence is significantly quenched by Sn(II) ions, and the effect can be used to determine Sn(II) ions. The highest fluorescence intensity is obtained at a concentration of 1.75 mM of C-dots in aqueous solution. The probe is highly selective and hardly interfered by other ions. The quenching mechanism appears to be predominantly of the static (rather than dynamic) type. Under optimum conditions, there is a linear relationship between fluorescence intensity and Sn(II) ions concentration up to 4 mM, and with a detection limit of 0.36 μM.